Comparative study of the two-shift fast break velocity index for the first three teams to qualify for the Golden Pistol of the Basketball Premier League (2016-2017) - نور الهدى ستار جبار; أ.د. هدى شهاب جاري (الرياضة المعاصرة)
The importance of the research is summarized in the study of comparing some of the kinematic variables of the quick attack with two shifts between the first three clubs of the golden pistol basketball in the Premier League (2016-2017), and the research problem is summarized in finding the strengths and weaknesses of the first three clubs of the golden pistol in the Premier League (2016-2017) in Basketball Therefore, the researcher decided to engage in a comparative study of some of the kinematic variables of the quick attack with two transfers to the top three clubs of the Golden Pistol of the Premier League for the year (2016-2017) in basketball.